SWOT analysis of cybersecurity vulnerabilities and strategies in renewable energy system: a case study on European wind power system - Azmi, Nor Nashrah; Abdul Rahim, Fiza; Hassan, Noor Hafizah; Ahmad, Nur Azfahani (Universiti Teknologi MARA, Perak, 2025)
As smart cities increasingly incorporate renewable energy systems to achieve sustainability objectives, ensuring strong cyber security measures is crucial. The susceptibility of these infrastructures, such as smart grids and solar panels, to diverse cyber threats poses significant risks to energy supply and data integrity. This paper examines cyber resilience in the context of the renewable energy industry, using a SWOT analysis of a European wind energy case study to assess the sector's cybersecurity posture and identify key vulnerabilities. This paper aims to identify the industry's current cyber defense mechanisms and the critical need to protect energy systems from increasingly sophisticated cyber threats that pose operational and safety risks, particularly in smart city infrastructures. The findings highlight the urgent need to bolster existing cyber defenses, develop comprehensive incident response plans, and foster a culture of collaborative information sharing among stakeholders. In the future, the paper suggests researching emergent technologies such as artificial intelligence and machine learning for real-time threat detection and adaptive cybersecurity in wind energy systems to strengthen adaptive cyber defensive capabilities and investigating quantum computing for its promise of superior encryption security. By addressing these research gaps, this study provides several recommendations for cyber resilience strategies that may be used to strengthen the cyber resilience of renewable energy systems, ensuring a secure and renewable energy supply for smart cities in the future.